A bioeconomic foundation for the nutrition-based efficiency wage model - Carl-Johan Dalgaard; Holger Strulik (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2008)
Drawing on recent research on allometric scaling and energy consumption, the present paper develops a nutrition-based efficiency wage model from first principles. The biologically micro-founded model allows us to address empirical criticism of the original nutrition-based efficiency wage model. By extending the model with respect to heterogeneity in worker body size and a physiologically founded impact of body size on productivity, we demonstrate that the nutrition-based efficiency wage model is compatible with the empirical regularity that taller workers simultaneously earn higher wages and are less likely to be unemployed in less developed economies. The theory also provides an answer to the question of why such regularity may disappear in the process of development.
Keywords: O11; O15; J21; J31; 330; Efficiency Wages; Nutrition; Metabolism; Allometric Scaling; Body Size; Effizienzlohn; Ernährung; Lebensstandard; Bioökonomik; Theorie